(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: telephone consultation services included in pediatric palliative care programs (PPC), contribute to solving some problems, and sometimes decrease in-person consultations. Objective: describe the telephone consultations received by the Pediatric Palliative Care Unit of the Pereira Rossell Children’s Hospital Center (UCPP-CHPR), their level of resolution and satisfaction degree with the consultation. Materials and methods: prospective, descriptive study taking place from 8/1-9/30/2019; review of call records received and subsequent telephone survey. All queries received were included. We analyzed demographic variables, reason for the call (administrative, need for intervention), level of satisfaction with the response, success in decreasing in-person consultation. Results: we recorded 93 telephone consultations from 53 people; median age 34 years, women: 48/53; mothers: 35; origin: South of the country 77; urban centers: 64; reasons for consultation: administrative 53/93 (request for drugs/ medical supplies 30, schedule consultation 14, request for transfers 9); need for intervention 40/93 (discomforting symptoms 12, problems with prosthetics 8, doubts about drugs 6, nursing care 6, psycho-emotional or social problems 4). According to the people surveyed the telephone consultation saved an in-person consultation 66/93, expressed satisfaction with the answers 91/93. Conclusions: the high number of administrative consultations, the possibility of decreasing in-person consultations, and the satisfaction levels reported by parents and caregivers indicate that telephone consultations are a resource to consider, systematize and improve in order to provide a more comprehensive care for children with health conditions that may require palliative care.